COMPARISON OF EFFICACY OF NSAIDS WITH INTRA- ARTICULAR INJECTION OF CORTICOSTEROIDS IN PATIENTS OF TEMPOROMANDIBULAR DISORDER (TMD) WITH INTERNAL DISC DISPLACEMENT WITHOUT REDUCTION (DDWOR) - Liaqat, Amna; Rubina Sheikh,; Fatimah Zahra Zia,; Muhammad Umar,; Hina Jabeen, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Temporomandibular disorders (TMD) are a diverse set of musculoskeletal and neuromuscular problems involving the temporomandibular joint complex and surrounding muscles 1. TMD prevalence has varied from one location to the next, with estimates ranging from 6 to 68 % in various types Objectives were to compare the efficacy of NSAIDs with intra-articular injection of corticosteroids in patients suffering from temporomandibular disorders (TMD) due to disc displacement without reduction in terms of mean pain score and mean mouth opening. This Randomized control trial was conducted at the Oral & Maxillofacial Surgery Department, PMC Dental institute, Faisalabad Medical University, Faisalabad, Pakistan, from 6th April 2018 to . 6th April 2019. Methods: All the diagnosed cases of temporomandibular disorder due to disc displacement without reduction were included. Study group (Group1) was injected with 1ml of Triamcinolone acetonide 40mg/ml once, every three weeks & Control group (Group 2) was given Naproxen 550 mg two times a day for 3 weeks. Pain and mouth opening were assessed at initial presentation & then after 3 weeks interval. Results: Total 80 patients were enrolled in the study (40 in each group). The mean age of patients in Control group was 28.73±4.88 years and in study group was 28.68±4.89 years. From 80 patients, 51 (63.80%) were females and 29 (36.20%) were males with 3:1 female to male ratio. Mean pain score was 4.18±0.93 in group 1 and 2.65±0.74 in group 2 after 3 weeks with p-value of 0.0011. Mean mouth opening after 3 weeks was seen as 34.93±1.82 mm in group 1 and 32.28±1.75 mm in group 2 with p-value of 0.0015. Conclusion: Intra-articular injections of corticosteroids are better than NSAIDs in reducing pain and improving mouth opening in patients suffering from TMD due to DDwoR.